First Letter of Paul to the Corinthians - Holladay, Carl R. (Living Word Commentary, 1979)
This commentary was part of a series called the Living Word Commentary. These volumes are designed for lay readers to give them an overview of the critical issues in various books of the Bible. In addition to commentary, this volume offers an overview of the church in Corinth, the setting, and occasion of Paul's letter to the congregation.